Difficulties faced by caregivers and family members of patients under palliative care at home: a literature review (Research, Society and Development, 2021)
With technological and intervention advances, medical services have significantly advanced, leading patients and their families to obtain new expectations, with regard to the outcome in a situation of chronic illness. However, due to sociocultural factors, health treatments are often conditioned exclusively on the hospital environment. Placing both the patient, team and family in a fragile condition when it comes to diseases considered incurable, where there is nothing left to do but wait. In this context, in order to minimize this waiting process in view of the certainty of death, the Ministry of Health (MS) implemented palliative care protocols in Hospital Institutions. Palliative Care protocols were created in 2002, due to the need to establish a look focused on humanized and integrated care for terminally ill patients. This study aims to: Know the difficulties faced by caregivers and family members of patients under palliative care at home. Through a literature review, with searches performed in articles published from 2016 to 2021. At the end of the study, it is understood that palliative care, when used from the onset of the disease, contributes to a better quality of life for the patient, to an appreciation of life, which brings the concept of meaning, that is, the sense and conviction of a purposeful life, where each one plays a role, with living understood as God's gift, lived in all its dimension, and the control and relief of pain and other symptoms. When answering the guiding question of the research, we saw in the studies that, in most cases, caregivers take a very large burden on themselves when having to take care of a family member with fear of imminent death, in addition to the suffering of the family member, having to take care of the housework and even worrying about their economic issue, because the family income is too small to maintain the care of that person, and of the rest of the family members.